A Modified Design of Mobile Water Plant Remover Device - ALIAS, MUHAMMAD ZAKI; ABU TALIB, SITI HIDAYAH (Recent Trends in Civil Engineering and Built Environment, 2023)
Invasive aquatic plants usually grow in lakes that are not the original habitat of invasive plants in the area. These invasive aquatic plants spread to new areas and can live anywhere in the water, whether emerging, submerged, or floating. Therefore, lake conservation should be done in a planned manner. The aim of the research is to find a solution to the university's concerns with lake clean-up. The problem of rapidly growing invasive plants has caused the university to incur high cleaning costs. The university hired a contractor to clean the lake and the method used was manual cleaning where the workers boarded a boat and cut plants using blades. Therefore, this study was conducted to modify the design of the subsurface water device and produce a user-friendly prototype device for plant removal. The prototype is designed with two combinations of tools available namely the Razer Weed and the Razer Rake. This prototype will be tested for its effectiveness in a designated study area. At the end of this study, it was found that the differences between the use of manual and prototype affect the time and cost where is the time required by the prototype is longer to clean invasive aquatic plants and the cost used is lower than the manual method. As a conclusion, the prototype was successfully produced and it is user-friendly beside can be used by the university in the future.